STUDY OF THERMAL ENVIRONMENT IN HOSPITAL GYMNASIUMS OF REHABILITATION - Célia Rodrigues (2013)
In hospital gymnasiums of rehabilitation, thermal environmental conditions represent a transversal risk factor to all occupants (patients, professionals) and with great impact on the sustainability of these institutions. In order to evaluate the thermal comfort conditions, in these places, we analyzed three gymnasiums of rehabilitation of patients. The results revealed situations of discomfort, according to the index values PPD / PMV. It is necessary to analyze these situations, carefully, to minimize energy consumption and improve the thermal comfort of occupants.